A New Application of a Wider Class of Power Increasing Sequences. (15th June 2021) - Bor, Hüseyin
Abstract: In the present paper, we have proved a basic theorem on the absolute Riesz summability factors of infinite series by using a wider class of power increasing sequences and then we applied this new result to the trigonometric Fourier series. Some new results are also obtained concerning the factored infinite series and trigonometric Fourier series.